Pediatric multiple sclerosis: Clinical features and outcome. (30th August 2016) - Waldman, Amy; Ness, Jayne; Pohl, Daniela; Simone, Isabella Laura; Anlar, Banu; Amato, Maria Pia; Ghezzi, Angelo
Abstract : Multiple sclerosis (MS) in children manifests with a relapsing-remitting MS (RRMS) disease course. Acute relapses consist of new neurologic deficits persisting greater than 24 hours, in the absence of intercurrent illness, and occur with a higher frequency early in the disease as compared to adult-onset RRMS. Most pediatric patients with MS recover well from these early relapses, and cumulative physical disability is rare in the first 10 years of disease. Brainstem attacks, poor recovery from a single attack, and a higher frequency of attacks portend a greater likelihood of future disability. Although prospective pediatric-onset MS cohorts have been established in recent years, there remains very limited prospective data detailing the longer-term clinical outcome of pediatric-onset MS into adulthood. Whether the advent of MS therapies, and the largely off-label access to such therapies in pediatric MS, has improved prognosis is unknown. MS onset during the key formative academic years, concurrent with active cognitive maturation, is an important determinant of long-term outcome, and is discussed in detail in another article in this supplement. Finally, increasing recognition of pediatric MS worldwide, recent launch of phase III trials for new agents in the pediatric MS population, and the clear imperative to more fully appreciate health-related quality of life in pediatric MS through adulthood highlight the need for standardized, validated, and robust outcome measures.